Biological filter stations: a new artificial reef concept to combat the effects of eutrophication in coastal seas - Stachowitsch, Michael (Annales. Series historia naturalis, 1998)
Shallow coastal waters are the most important marine ecosystems, both ecologically and economically. They are also the most endagered, with eutrophication increasingly being recognized as one of the greatest threats. The present contribution proposes to combat not only the major symptoms of eutrophication - decreased water transparency, excessive algal blooms, mucus production, and oxygen deficiency - but also the causes by utilizing the natural filter-feeding capacity of marine organisms can settle and grow...
Keywords: Adriatic Sea; ekologija morja; ekosistemi; evtrofikacija; hidrobiologija; Jadransko morje; morje; sea